PENGARUH CONTENT MARKETING , VIRAL MARKETING DAN INFLUENCER TERHADAP MINAT BELI PRODUK SKINCARE PADA MAHASISWA - Pasaribu, Aisyah Fitri; Fadhila Rahma, Tri Inda; Dharma, Budi (ECOBISMA (JURNAL EKONOMI, BISNIS DAN MANAJEMEN), 2023)
Abstract : This study aims to determine the effect of Content Marketing, Viral Marketing and Influencers on Buying Interest in Students. This type of research is quantitative with a questionnaire distribution method. Respondents in this study were 100 students from the Faculty of Economics and Islamic Business, State Islamic University of North Sumatra. The technique used is purposive sampling. The method used in this research is variance-based Structural Equation Modeling (SEM) analysis, namely Patrial Least Square (PLS). The results of this study indicate the influence of Viral Marketing on Buying Interest in Skincare Products. While the Content Marketing and Influencer Variables show no influence on the Interest in Buying Skincare Products in Students.